Breastfeeding Support and Counseling: A Practical Guide for the General Practitioners in Outpatient Clinics (International Journal of Studies in Nursing, 2018)
Many studies have cited the need for more time and adequate training in breastfeeding (BF) support and counseling for health care professionals in the outpatient setting. As a pediatric nurse practitioner, primary care provider (PCP), and an International Board Certified Lactation Consultant (IBCLC), this dilemma is well understood. With the establishment of baby-friendly hospitals, BF mothers receive the much needed BF counseling and support before going home. However, the length of hospital stays for mothers with healthy, full-term newborns (NBs) has dramatically decreased with the advancement of technologies in the healthcare field. Grassley, Schleis, Bennett, Chapman and Lind (2014) found that 38% of NBs whose mothers planned to exclusively breastfeed (BF) received formula before hospital discharge in their retrospective review of 302 hospital charts. Professional BF support in the outpatient setting is inadequate or insufficient. The first 2 weeks of life are crucial to the continuation of exclusive breastfeeding (EBF) or its termination. Most NBs are seen for hospital discharge follow-up within 5 days. PCPs have the ideal opportunity to address BF support and/or counseling at this crucial time with BF mothers and their support person(s) to promote, sustain, and maintain EBF.